Methodological frameworks for strategic planning of socio-economic development at the regional level - Hordiienko, V.; Kalashnykova, T. (Економічний вісник Донбасу, 2018)
The article summarizes the scientific and methodological foundations of strategic planning of socio-economic development at the regional level. The main objective of strategic planning of regional development is specified. The main stages of working out the forecast system for the development of the economy of the regions are considered. The process of developing a strategic plan for the region’s socio-economic development is analyzed. The factors influencing the process of strategy development are considered. У статті узагальнено науково-методичні засади стратегічного планування соціально-економічного розвитку на регіональному рівні. Визначена основна мета стратегічного планування регіонального розвитку. Розглянуто основні етапи розробки системи прогнозів розвитку економіки регіонів. Проаналізовано процес розробки стратегічного плану соціально-економічного розвитку регіону. Розглянуто фактори, які впливають на процес розробки стратегії. В статье обобщены научно-методические основы стратегического планирования социально-экономического развития на региональном уровне. Указана основная цель стратегического планирования регионального развития. Рассмотрены основные этапы разработки системы прогнозов развития экономики регионов. Проанализирован процесс разработки стратегического плана социально-экономического развития региона. Рассмотрены факторы, влияющие на процесс разработки стратегии.